The Economics of Central Luzon Dry Season Irrigation Scheme - Bimbao, Gaspar Britania (1984)
This study was undertaken to evaluate the impact of Camiling River Irrigation System (CamRIS) in Central Luzon, Philippines on the total dry season paddy production, the resource use efficiency, the level and distribution of paddy incomes; and to examine the factors which determined the extent of paddy cultivation by farmers under the scheme. Results of the study revealed that the mean area cultivated and yield per hectare increased significantly under the scheme, hence, the total area planted, production and cropping intensity. Nevertheless, the scheme failed to reduce the variability of these factors among the various sections of CamRIS. Farmers considered seeds, hired labour and total labour among other inputs of utmost importance in attaining higher paddy production under the scheme as only in these inputs that expenditure per hectare significantly increased. Nevertheless, the paddy net income before and after the scheme were not significantly different. In addition, the scheme failed to reduce income inequality among the farmer-participants as depicted by their almost identical Lorenz curves before and after the scheme and corroborated b y the equal values of their Gini coefficients of 0.47. Resource use efficiency analysis revealed that expenditures on seeds and family labour were adjusted to their optimum values after the scheme. In contrast to fertilizers which were allocated efficiently before and after the scheme, expenditure allocations on chemical in puts for crop protection and hired labour were inefficient as indicated by their ratios of marginal value products to factor costs which were significantly less than unity. Thus, reducing the allocation of these inputs would have increased- their production efficiencies. Regression analysis showed that the profitability of dry season irrigated farming and the availability of family and hired labour were the major determinants the in farmers' decision to increase paddy cultivation under the scheme. On the other hand, working capital carried forward from the wet season, tenure status, non-mechanisation of land preparation were factors that worked against the farmers to increase their paddy cultivation.